Evaluation of radio propagation techniques for hierarchical sensor networks - Bello-Salau, H; Salami, A. F.; Anwar, Farhat; Aibinu, Abiodun Musa (2011)
Recent advances in the field of wireless sensor network technology and sensor instrumentation have led to the evolvement of new protocols, which are specially designed for wireless sensor networks where energy conservation is of paramount importance. Researchers in the field of wireless sensor networks are currently concentrating on the challenge of designing an optimum routing protocol, since they might differ depending on the application and network architecture used in their design. Hierarchical routing protocols for large-scale wireless sensor networks are more advantageous compared to other types of routing techniques. This paper is an evaluation of selected hierarchical routing protocols with special emphasis on their radio propagation techniques efficiency for hierarchical Sensor Networks.